Conservative Treatment of Bisphosphonate-Related Osteonecrosis of the Jaw in Multiple Myeloma Patients - Pelagia I. Melea; Ioannis Melakopoulos; Efstathios Kastritis; Christina Tesseromatis; Vasileios Margaritis; Meletios A. Dimopoulos; Evangelos Terpos (International Journal of Dentistry)
The use of intravenous bisphosphonates (pamidronate or zoledronic acid) is the cornerstone for the management of multiple myeloma-(MM-) related bone disease. However, osteonecrosis of the jaw (ONJ) is a rare, but sometimes difficult to manage, adverse effect of bisphosphonates therapy. A retrospective review of all MM patients who were treated with bisphosphonates in our department, from 2003 to 2013, and developed ONJ was performed. According to inclusion criteria, 38 patients were studied. All these patients were treated as conservatively as possible according to the American Association of Oral and Maxillofacial Surgeons criteria. Patients were managed with observation, oral antibacterial mouth rinse with chlorhexidine, oral antibiotics, pain control with analgesics, nonsurgical sequestrectomy with or without simultaneous administration of antibiotics, or major surgery with or without antibiotics. Healing of the lesions was achieved in 23 (60%) patients who were treated with conservative measures; the median time to healing was 12 months (95% CI: 4–21). The number of bisphosphonates infusions influenced the time to healing: the median time to healing for patients who received <16 infusions was 7 months and for those with >16 infusions was it 14 months P=0.017. We conclude that a primarily nonsurgical approach appears to be a successful management strategy for bisphosphonate-related ONJ.